2009
DOI: 10.1152/ajpcell.00620.2008
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines regulate E-cadherin transcription through c-Myc modulating intestinal epithelial barrier function

Abstract: The integrity of the intestinal epithelial barrier depends on intercellular junctions that are highly regulated by numerous extracellular and intracellular factors. E-cadherin is found primarily at the adherens junctions in the intestinal mucosa and mediates strong cell-cell contacts that have a functional role in forming and regulating the epithelial barrier. Polyamines are necessary for E-cadherin expression, but the exact mechanism underlying polyamines remains elusive. The current study was performed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 59 publications
1
52
0
Order By: Relevance
“…Our previous studies (24,47) have shown that regenerative gastric and duodenal mucosa after stress is associated with increased expression of the c-Myc gene following increased levels of cellular polyamines and that inhibition of c-Myc expression by polyamine depletion decreases cell renewal and delays mucosal healing. Our results further show that induced c-Myc forms dimers with Max after injury and specifically binds to the DNA sequence in the promoter of its target genes such as p21 and E-cadherin (21,22,23). Because polyamines are necessary but not sufficient for the stimulation of c-Myc expression (22,23), an open question is which cellular signaling or factors initially activate c-Myc gene transcription after GI mucosal injury.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Our previous studies (24,47) have shown that regenerative gastric and duodenal mucosa after stress is associated with increased expression of the c-Myc gene following increased levels of cellular polyamines and that inhibition of c-Myc expression by polyamine depletion decreases cell renewal and delays mucosal healing. Our results further show that induced c-Myc forms dimers with Max after injury and specifically binds to the DNA sequence in the promoter of its target genes such as p21 and E-cadherin (21,22,23). Because polyamines are necessary but not sufficient for the stimulation of c-Myc expression (22,23), an open question is which cellular signaling or factors initially activate c-Myc gene transcription after GI mucosal injury.…”
mentioning
confidence: 52%
“…Our results further show that induced c-Myc forms dimers with Max after injury and specifically binds to the DNA sequence in the promoter of its target genes such as p21 and E-cadherin (21,22,23). Because polyamines are necessary but not sufficient for the stimulation of c-Myc expression (22,23), an open question is which cellular signaling or factors initially activate c-Myc gene transcription after GI mucosal injury.…”
mentioning
confidence: 52%
“…We therefore speculated that microtubule disruption affects the positive regulatory pathways that result in the induction of E-cadherin mRNA. c-MYC is one of the down-stream transcription factors regulated by TGF-b and reported to be an E-cadherin transcriptional activator (Batsche et al, 1998, Liu et al, 2009, Pietenpol et al, 1990. We have shown that strong c-MYC signals were maintained even at 48 h in the MEE treated with NDZ, which was associated with its down-stream target ID2 induction.…”
Section: Discussionmentioning
confidence: 81%
“…E-cadherin transcription is tightly regulated through the promoter that contains a CAAT box, a GC rich region and an E-box. The transcription factor c-MYC transactivates E-cadherin through its direct interaction with the E-box or as a co-activator of AP-2 transcription factor, which interacts with the GC-rich region (Batsche et al, 1998, Liu et al, 2009. TGF-b negatively regulates c-MYC (Pietenpol et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The polyamines from the metabolism of L-arginine or L-ornithine have important roles in the growth, development, and repair of intestinal mucosa (35)(36)(37). The beneficial effects of polyamines on intestinal mucositis (38) and in the regulation of protein expression and members of the tight junctions (39,40) were related. However, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%